Paravertebral and Retroperitoneal Vascular Tumour Presenting with Kasabach-Merritt Phenomenon in Childhood, Diagnosed with Magnetic Resonance Imaging - Gonca Keskindemirci; Deniz Tuğcu; Gönül Aydoğan; Arzu Akçay; Nuray Aktay Ayaz; Ali Er; Ensar Yekeler; Bilge Bilgiç (Hindawi Limited, 2015)
Kasabach-Merritt phenomenon (KMP) is characterized by vascular tumour and consumptive coagulopathy with life-threatening thrombocytopenia, prolonged prothrombin time and partial thromboplastin time, hypofibrinogenemia, and the presence of high fibrin split products. We report a case of 3-year-old boy with local aggressive vascular lesions associated with KMP. Magnetic resonance imaging revealed an extensive lesion at paravertebral and retroperitoneal regions that was infiltrating vertebrae. Although we did not get any response to steroid or propranolol treatment, partial response was observed radiologically with interferon-alpha treatment. Unfortunately, the patient died because of the uncontrolled consumptive coagulopathy that led to intracranial hemorrhage which was caused by huge knee hematoma after minor trauma.